Acute-phase proteins and oxidative stress in patients undergoing coronary artery bypass graft: comparison of cardioplegia strategy - Plicner, Dariusz; Stoliński, Jarosław; Rzucidło-Hymczak, Anna; Kapelak, Bogusław; Undas, Anetta (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Introduction: Several strategies are still being introduced to cardiac surgery techniques to reduce the signs of the inflammatory response and oxidative stress. Many efforts have been made to develop the best possible method for myocardial protection. Aim : To assess the effect of the cardioplegia strategy on the systemic inflammatory response and oxidative stress. Material and methods : A group of 238 consecutive, elective on-pump coronary artery bypass graft patients (CABG; 183 men, aged 64.6 ±8.1 years) were prospectively studied. Patients were enrolled in two groups: with warm blood cardioplegia (n = 124) and with cold crystalloid cardioplegia (n = 114). In each group, pre- and postoperative levels of plasma C-reactive protein, fibrinogen, interleukin 6 and 8-iso-prostaglandin F 2α (8-iso-PGF 2α ) were measured. Results : All studied markers significantly increased 18–36 h following CABG and then decreased in 5–7 postoperative days but remained above baseline levels. No differences in terms of studied markers and clinical outcomes were noted for the different types of cardioplegia. Regression analysis showed a significant correlation between preoperative level of oxidative stress measured by 8-iso-PGF 2α and postoperative myocardial infarction as well as in-hospital cardiovascular death (p = 0.047 and p = 0.041 respectively). Conclusions : This study extends previous reports by showing that the type of cardioplegia does not affect the systemic inflammatory response or oxidative stress, which are associated with the CABG procedure. It might be speculated that preoperative screening of oxidative stress could be helpful in identifying patients at increased risk of an unfavorable course after CABG.